The correlation between non-suicidal self-injury in adolescents, parenting styles, and borderline personality traits - Dai, Yuanyuan; Yang, Ping; Ji, Wensai; Diao, Liang; Han, Lu (Frontiers in Psychiatry, 2025)
IntroductionThis study aimed to investigate the associations between parenting styles, borderline personality traits, and non-suicidal self-injury (NSSI) in adolescents with depression, thereby providing a theoretical foundation for targeted psychological interventions.MethodsThis study included 101 adolescent patients with depressive episodes admitted to the Fourth People’s Hospital of Wuhu City, Anhui Province, from May 2022 to October 2023 (23 males and 78females). Two attending physicians or those of higher ranks diagnosed these patients as having depressive episodes based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5).Data were collected using the Adolescent Non-Suicidal Self-Injury Behavior Assessment Questionnaire, the Parental Rearing Style Evaluation Scale, and relevant items from the Borderline Personality Questionnaire for survey administration.ResultsThe frequent NSSI group showed significantly higher scores than the non-frequent group in paternal rejection/denial, maternal overprotection/interference, and total borderline personality traits (all P<0.01, Cohen’s d>0.2). Additionally, the frequent NSSI group exhibited greater paternal overprotection and maternal rejection/denial (both P<0.05, Cohen’s d>0.2). Significant positive correlations were observed between NSSI scores and paternal rejection/denial, maternal overprotection/interference, maternal rejection/denial, and borderline personality traits (all P<0.01), while paternal overprotection was positively correlated with NSSI scores (P<0.05). Multivariate analysis identified paternal rejection/denial, maternal overprotection/interference, and borderline personality traits as independent risk factors for NSSI behaviors (all P<0.05).ConclusionThese findings suggest that paternal rejection and denial, maternal overprotection and interference, and borderline personality traits may be associated with adolescent NSSI behaviors. The results provide valuable insights for clinicians to better understand the psychosocial contributing factors of NSSI, highlighting that future intervention strategies should consider the combined effects of family parenting patterns and adolescents’ personality characteristics. This study employed a cross - sectional design, which rendered it impossible to establish the multiple causal relationships among parental parenting styles, borderline personality traits, and non - suicidal self - injury (NSSI) behaviors, as well as to analyze the mediating effects between these variables. Future research could integrate multiple research methodologies, such as combining cross - sectional and longitudinal studies.